2021
DOI: 10.1097/ju.0000000000001967.02
|View full text |Cite
|
Sign up to set email alerts
|

Pd03-02 racial Disparities in Prostate Cancer Treatment in a Multi-Institutional Regional Collaborative

Abstract: INTRODUCTION AND OBJECTIVE: Symptomatic urinary stone disease is a common cause for emergency department (ED) visits; for some patients, ED revisits often occur before cessation of a stone episode. Little is known regarding how non-clinical factors such as patient race, ethnicity, or insurance status contribute to ED revisit for stone disease. We sought to identify associations between ED revisit and patient race/ethnicity.METHODS: This was a retrospective cohort study of patients in Florida, Georgia, and Mary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[131][132][133][134] For example, a multi-institutional study of the impact of the COVID-19 pandemic on prostate cancer treatment found that Black men experienced a 94% drop in surgery compared with no disruption in White men. 135 Despite fairly strong evidence that Black men have equivalent or higher prostate cancer-specific survival within an equal-access health care system such as the Veterans Health Administration, 52,136,137 a recent Veterans Health Administration study found that, among patients who were most likely to benefit from definitive treatment, Black men were 11% less likely than non-Black men to receive it. 138 Although there is some evidence that aggressive prostate cancer is more common in Black men, 131,139 these findings may be confounded by differences in access to high-quality treatment.…”
Section: Prostatementioning
confidence: 99%
See 1 more Smart Citation
“…[131][132][133][134] For example, a multi-institutional study of the impact of the COVID-19 pandemic on prostate cancer treatment found that Black men experienced a 94% drop in surgery compared with no disruption in White men. 135 Despite fairly strong evidence that Black men have equivalent or higher prostate cancer-specific survival within an equal-access health care system such as the Veterans Health Administration, 52,136,137 a recent Veterans Health Administration study found that, among patients who were most likely to benefit from definitive treatment, Black men were 11% less likely than non-Black men to receive it. 138 Although there is some evidence that aggressive prostate cancer is more common in Black men, 131,139 these findings may be confounded by differences in access to high-quality treatment.…”
Section: Prostatementioning
confidence: 99%
“…The larger disparity in prostate cancer mortality compared with incidence likely reflects less access to high‐quality treatment, which continues to be documented in Black men 131‐134 . For example, a multi‐institutional study of the impact of the COVID‐19 pandemic on prostate cancer treatment found that Black men experienced a 94% drop in surgery compared with no disruption in White men 135 . Despite fairly strong evidence that Black men have equivalent or higher prostate cancer‐specific survival within an equal‐access health care system such as the Veterans Health Administration, 52,136,137 a recent Veterans Health Administration study found that, among patients who were most likely to benefit from definitive treatment, Black men were 11% less likely than non‐Black men to receive it 138 .…”
Section: Selected Cancer Sitesmentioning
confidence: 99%
“…A later stage makes prostate cancer more difficult to treat and is associated with an increased risk of relapse. At the start of the COVID-19 pandemic, there had also been a shift in cancer resource allocation which consequently made it less likely for black men to receive prostatectomy [ 21 ]. Furthermore, they are less likely to have health insurance, access to high-quality care, and more likely to have a lower socioeconomic status [ 19 ].…”
Section: Discussionmentioning
confidence: 99%